(untitled) (Journal of Engineering, 2017)
A tungsten inert gas (TIG) welding is one of the most popular kinds of welding used to join metals mainly for aluminum alloys. However, many challenges may be met with this kind of joining process; these challenges arise from decay of mechanical properties of welded materials. In the present study, an attempt was made to enhancing the mechanical properties of TIG weld joint of 6061-T6 aluminum alloy by hardening the surfaces using shoot peening technique. To optimize the shoot peening process three times of exposure (5, 10, and 15) min. was used. All peened and unpeened, and welded and unwelded samples were characterized by metallographic test to indicate the phase transformation and modification in microstructure occurring during welding process. Tensile test and Vickers micro-hardness measurements were performed for all samples to investigate the effect of shoot peening on mechanical properties of welded aluminum. The results indicated a significant improvement in properties for peened welded and unwelded samples compared with those unpeened one. Also, the results showed that the tensile and microhardness properties were increased with increasing the time of exposure to 15 min. due to generation of compressive residual stresses at surface.